2014
DOI: 10.1136/openhrt-2014-000136
|View full text |Cite
|
Sign up to set email alerts
|

Calcific extension towards the mitral valve causes non-rheumatic mitral stenosis in degenerative aortic stenosis: real-time 3D transoesophageal echocardiography study

Abstract: ObjectiveMitral annular/leaflet calcification (MALC) is frequently observed in patients with degenerative aortic stenosis (AS). However, the impact of MALC on mitral valve function has not been established. We aimed to investigate whether MALC reduces mitral annular area and restricts leaflet opening, resulting in non-rheumatic mitral stenosis.MethodsReal-time three-dimensional transoesophageal images of the mitral valve were acquired in 101 patients with degenerative AS and 26 control participants. The outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Endomyocardial fibrosis is characterized by the presence of fibrous tissue in the endocardium eventually extending into the myocardium, a finding not identified in our patient. Mitral annular and leaflet calcification occurs frequently with degenerative aortic stenosis and is known to reduce leaflet opening and result in significant mitral stenosis in 25% of patients with calcific aortic stenosis [11]. In our patient, however, no involvement of the mitral valve was noted.…”
Section: Discussionmentioning
confidence: 43%
“…Endomyocardial fibrosis is characterized by the presence of fibrous tissue in the endocardium eventually extending into the myocardium, a finding not identified in our patient. Mitral annular and leaflet calcification occurs frequently with degenerative aortic stenosis and is known to reduce leaflet opening and result in significant mitral stenosis in 25% of patients with calcific aortic stenosis [11]. In our patient, however, no involvement of the mitral valve was noted.…”
Section: Discussionmentioning
confidence: 43%
“…Hung et al showed that if there is papillary muscle displacement outside of the mitral annulus after ring annuloplasty for IMR, MR persists due to persistent abnormal leaflet tethering due to restricted posterior leaflet motion [ 49 ]. Lastly, Iwataki et al studied the effect of extension of calcification to the mitral valve leaflet in patients with aortic stenosis and found that this condition can result in significant non-rheumatic mitral stenosis with decreased leaflet opening and mitral annular area [ 50 ].…”
Section: Applications Of 3dementioning
confidence: 99%
“…6 As the disease process continues, the dystrophic calcification extends into the left ventricular (LV) inflow tract and onto the MV leaflets, thereby obstructing LV inflow (Figure 1). 7 This disease process has increasingly been recognized as degenerative MS (DMS).…”
Section: Introductionmentioning
confidence: 99%